Effect of Transition Metal Ions on the Hydrolysis of the Methyl Derivatives of Salicylanil - Prabhu, D.V.; Laxmeshwar, N.B. (Asian Journal of Chemistry, 2010)
The catalytic effect of Ni(II), Zn(II) and Cu(II) ions on the hydrolysis of the methyl derivatives of salicylanil has been studied at pH-4.58 at 35ºC. The hydrolysis follows the sequence meta > para > ortho in the absence and presence of metal ions. The presence of metal ions accelerates the hydrolysis rate according to the sequence Ni(II) > Zn(II) > Cu(II) which is in accordance with the Irving and Williams order of stability constants of metal chelates involving nitrogen and oxygen donor ligands. The initial retardation of rate of hydrolysis observed at lower Cu(II) concentrations has been explained as due to Jahn-Teller distortion of the metal complex to achieve stability. A suitable reaction mechanism has been suggested for the metal ion-catalysed hydrolysis of the imines under study.